1985
DOI: 10.7863/jum.1985.4.9.475
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular size in newborn infants.

Abstract: Cranial ultrasound examinations were performed on 533 infants of between 48 and 96 hours of age to establish the range of ventricular size in neonates of different gestational ages in whom there was no evidence of intraventricular hemorrhage or neural tube defects. It was found that ventricular size did not vary in infants with gestational age of 26 weeks or more. Only 15 (2.8 per cent) neonates had a ventricular width of greater than 3 mm. Of these 15 infants, 13 were re-examined within the first year of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 0 publications
5
30
1
Order By: Relevance
“…The inclusion of fewer extremely premature infants in both studies and the lower transducer resolution in the 1980s may account for the small differences between the previous and present reference values. Reference intervals for the AHW ( Յ 3 mm) are in line with earlier studies ( 4, 7,8,10 ). Literature regarding the size of the occipital horns is inconclusive; previous reported upper limits for the TOD range from 7 mm for the most premature infants up to 24.7 mm ( 7,9,10 ).…”
Section: Discussionmentioning
confidence: 58%
“…The inclusion of fewer extremely premature infants in both studies and the lower transducer resolution in the 1980s may account for the small differences between the previous and present reference values. Reference intervals for the AHW ( Յ 3 mm) are in line with earlier studies ( 4, 7,8,10 ). Literature regarding the size of the occipital horns is inconclusive; previous reported upper limits for the TOD range from 7 mm for the most premature infants up to 24.7 mm ( 7,9,10 ).…”
Section: Discussionmentioning
confidence: 58%
“…Although most of the subjects described in these studies have a small amount of visible CSF at the location of measurement, the finding of slitlike ventricles, in which little to no CSF is seen in the ventricle at the location of measurement, is informally described in all three investigations [11][12][13] …”
Section: Methodsmentioning
confidence: 98%
“…It is in line with our results. Perry et al (9) reported that AHW between 3 and 5 mm was not associated with neurodevelopmental impairment at a single follow up visit in 13 infants during the first year of life; however, Govaert et al (15) reported that values exceeding 6 mm, are associated with ventricular ballooning and suggest the need for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate diagnosis of ventricular abnormality in preterm neonates is based on a good comprehension of normal and abnormal values, and it saves the time for rapid intervention. Available data on the reference curves are limited (5)(6)(7)(8)(9)(10)(11). Significant variation exists between the studies with respect to patient characteristics sample size, measured parameters, and timing of sonography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation